Situation Report: Romania, 18 March 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Soviet-Romanian Agreement on Joint Construction of Nuclear Power Plant Norwegian Foreign Minister's Good Will Visit to Romania Ceausescu to Attend UN Session Chairman of British Board of Trade in Romania Past Tendency to Ignore the Role of the Market Criticized Provisional Measures Affecting Wholesale Prices Literary Awards Again under Fire Personnel Changes Coverage of Brandt-Stoph Meeting in Erfurt